A comparison of frontal plane projection angle across landing tasks in female gymnasts - Comfort, P.; Colclough, A.; Herrington, L. (International Journal of Athletic Therapy & Training, 2016)
The aim of this study was to compare FPPA between three landing tasks and determine the reliability of FPPA in 15 competitive female gymnasts (age 13.5 ± 2.07 years). Reliability of FPPA was highest in the drop landing task, with no learning effect present. The backaway task showed the greatest FFPA (right: 26.75 ± 9.57°; left: 19.67 ± 9.03°), which was greater than the drop landing task (right: 19.07 ± 7.42°; left: 12.18 ± 4.83°). Individuals involved in training young female gymnasts are encouraged to screen for injury risk using FPPA during the drop landing task.